Antenatal testing for anaemia, HIV and syphilis in Indonesia – a health systems analysis of low coverage - Baker, C. (BMC Pregnancy Childbirth, 2020)
BACKGROUND: Adverse pregnancy outcomes can be prevented through the early detection and treatment of anaemia, HIV and syphilis during the antenatal period. Rates of testing for anaemia, HIV and syphilis among women attending antenatal services in Indonesia are low, despite its mandate in national guidelines and international policy. METHODS: Midwife-held antenatal care records for 2015 from 8 villages in 2 sub-districts within Cianjur district were reviewed, alongside the available sub-district Puskesmas (Community Health Centre) maternity and laboratory records. We conducted four focus group discussions with kaders (community health workers) (n = 16) and midwives (n = 9), and 13 semi-structured interviews with laboratory and counselling, public sector maternity and HIV management and relevant non-governmental organisation staff. Participants were recruited from village, sub-district, district and national level as relevant to role. RESULTS: We were unable to find a single recorded result of antenatal testing for HIV, syphilis or anaemia in the village (566 women) or Puskesmas records (2816 women) for 2015. Laboratory records did not specifically identify antenatal women. Participants described conducting and reporting testing in a largely ad hoc manner; relying on referral to health facilities based on clinical suspicion or separate non-maternity voluntary counselling and testing programs. Participants recognized significant systematic challenges with key differences between the more acceptable (and reportedly more often implemented) haemoglobin testing and the less acceptable (and barely implemented) HIV and syphilis testing. However, a clear need for leadership and accountability emerged as an important factor for prioritizing antenatal testing and addressing these testing gaps. CONCLUSIONS: Practical solutions such as revised registers, availability of point-of-care tests and capacity building of field staff will therefore need to be accompanied by both funding and political will to coordinate, prioritize and be accountable for testing in pregnancy.